2008
DOI: 10.1002/ejoc.200701001
|View full text |Cite
|
Sign up to set email alerts
|

A Ruthenium‐Catalyzed Approach to the Friedländer Quinoline Synthesis

Abstract: In a modification of the Friedländer reaction, 2‐aminobenzyl alcohol is oxidatively cyclized with a variety of ketones to yield substituted quinolines. Of all the ruthenium catalysts that were tested for this reaction, the second‐generation Grubbs' catalyst gives the highest quinoline yield, in combination with KOtBu as a base. The presence of a hydrogen acceptor is required to regenerate the catalyst. Also the reaction mechanism is discussed, and the results show that there are possibly two different pathways… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(30 citation statements)
references
References 43 publications
0
30
0
Order By: Relevance
“…In addition, it was also demonstrated that ketones 1 were found to be coupled with aldehydes 6 to give coupled ketones 3 (Scheme , route d) 9. Several other transition metal precursors have also been introduced for such sp 3 ‐carbon–sp 3 ‐carbon bond‐forming reactions,10–16 and this coupling protocol could be applied to modified Friedländer quinoline synthesis 17–26. Prompted by these findings, this report describes another ruthenium‐catalyzed one‐pot multicatalytic coupling mode between secondary alcohols 5 and aldehydes 6 , leading to coupled ketones 3 or coupled secondary alcohols 4 by the tuning of the molar ratio of [ 5 ]:[ 6 ] and the presence (or absence) of a hydrogen acceptor (Scheme , routes e and f).…”
Section: Introductionmentioning
confidence: 90%
“…In addition, it was also demonstrated that ketones 1 were found to be coupled with aldehydes 6 to give coupled ketones 3 (Scheme , route d) 9. Several other transition metal precursors have also been introduced for such sp 3 ‐carbon–sp 3 ‐carbon bond‐forming reactions,10–16 and this coupling protocol could be applied to modified Friedländer quinoline synthesis 17–26. Prompted by these findings, this report describes another ruthenium‐catalyzed one‐pot multicatalytic coupling mode between secondary alcohols 5 and aldehydes 6 , leading to coupled ketones 3 or coupled secondary alcohols 4 by the tuning of the molar ratio of [ 5 ]:[ 6 ] and the presence (or absence) of a hydrogen acceptor (Scheme , routes e and f).…”
Section: Introductionmentioning
confidence: 90%
“…For instance, 2‐phenylquinoline is prepared by arylation of quinoline or 2‐chloroquinoline by ZnPh 2 , MgPh 2 , or PhB(OH) 2 in the presence of metal complex catalysts . 2‐Phenylquinoline can be prepared according to Friedländer by acid‐catalyzed cyclocondensation of о ‐nitrobenzaldehyde with acetophenone , by the reaction of о ‐aminobenzyl alcohol with acetophenone (or 1‐phenylethanol) in the presence of ruthenium catalysts or by aniline condensation with benzaldehyde and acrylic acid in the presence of a palladium catalyst .…”
Section: Introductionmentioning
confidence: 99%
“…This reaction provides an environmentally friendly route to the conversion of alcoholic functions to carbonyl groups and water is the only by‐product during the course of the reaction, which was removed using molecular sieves. The aldehydes and ketones36, 37 formed after 3–6 h of stirring were isolated and quantified as their 2,4‐dinitrophenylhydrazone derivatives 38. The relatively higher product yield obtained for the oxidation of cinnamyl alcohol was due to the presence of more acidic α‐CH unit in cinnamyl alcohol.…”
Section: Resultsmentioning
confidence: 99%